Implementasi UU Nomor 33 Tahun 2014 tentang Jaminan Produk Halal pada Produk Makanan Industri Kecil Menengah di Desa Ploso Kabupaten Pacitan - Rukoyah, Andriani Fitri; Ayu, Diyan Putri (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The use of halal labels is very important for domestic consumers whose majority of the population is Muslim. Law Number 33 of 2014 concerning Halal Product Guarantee explains that every product that will be marketed domestically needs to pass the halal certification process. In fact, the law has not been positively applied in Indonesia due to certain factors. The purpose of the research above this writing has problems, What is the legal responsibility of business actors facing consumers for MSME food products that are not halal certified? (2) How is BPOM responsible for MSME food products that have not been certified halal? (3) What is the role of the Pacitan government in standardizing halal products? This research uses qualitative research methods by observing the law and implementing small and medium-sized industrial food products in Tegalombo District, Pacitan Regency. In small and medium industrial food products in Pacitan, it will be analyzed using a descriptive analysis method, namely a qualitative method by collecting data using observation and interview methods that present an event or symptom systematically, factually and accurately. Based on this research, it was concluded that(1) producing halal food products by having a halal certificate in providing comfort, security, safety, and certainty for the community. (2) the withdrawal of products circulating in the market, the provision of administrative sanctions and confiscation without compensation with the functions of pre-market evalution and post-market control supervision. . (3) facilitating and assisting halal certification in the IKM food and beverage sector, conducting training and certification for halal providers, building halal product information systems through campaigns and festivals, and plans to establish a halal center within the East Java Provincial government.